Assessing the green roof technology in green building rating systems - Sheng, L.X.; Mohd Ariffin, A.R.; Hussein, H. (2011)
Green roofs or vegetated roofs are becoming popular for sustainable development. On one hand, research shows that green roofs have numerous environmental benefits such as reduce flood risk, improve rainwater runoff quality, mitigate urban heat island, building energy saving and provide urban wildlife habitat. On the other hand, the development and utilisation of green building rating systems are crucial to appraise existing and new green buildings. The research was conducted foreseeing that the criteria and weight of scoring in such rating systems certainly will influence built environment stakeholders’ decision in pursuing green building technologies. A sufficient weight of scoring in the rating system will stimulate the implementation of green roof technology for the construction projects that are adopting that particular green building rating system. However, insufficient weight of scoring will make green roof technology less attractive and eventually being left out in the sustainable development process even though this technology have the potential to mitigate current environmental issues. This paper explores the approach of assessing green building technologies based on rating systems to measure its performance and potential, with an aim to clarify the role and position of green roof technology in various green building rating systems including Leadership in Energy and Environmental Design (LEED), Green Building Index (GBI) and Singapore Building Construction Authority Green Mark. The research methodology involves analysing the relevance and scoring performance of green roof based on the criteria stated in green building rating systems such as sustainable site planning and management, materials and resources, water efficiency and innovation. This paper will also explore the approach of assessing